Enhancing tensile properties of carbon fiber-reinforced polypropylene composite using carbon Nanotube coating - Sayed Mohamed Zain, Sharifah Mazrah (2009)
Carbon fibers, when used without any surface treatments, will produce composites with low interlaminar shear strength (ILSS) which attributed largely to weak bonding between the fiber and the matrix. CNT-coating treatment was conducted to improve carbon fiber-matrix interfacial bonding. This treatment was done by growing carbon nanotubes (CNTs) directly on carbon fibers using chemical vapor deposition (CVD) to create CNT-coated carbon fibers. The objectives was to study the microscopic morphology of CNTs formation on the surface of carbon fibers at various treatment conditions, to study the interfacial shear strength (IFSS) of CNT-coated carbon fibers, tensile properties and thermal stability of CNT-coated carbon fiber composites as well as comparison with untreated and commercial carbon fibers. The CNTs were produced by a benzene-ferrocene gas reaction inside a high temperature tube furnace. The reaction temperature, the carrier gas flow rate and weight of ferrocene were varied at 700 oC, 800oC and 900oC; 100 ml/min and 300 ml/min; 0.3 g, 0.5 g and 1.0 g respectively and the reaction time for CNT growth was set at 30 minutes. The microscopic morphology of CNTs formation on the surface of carbon fibers was observed using scanning electron microscopy (SEM) and transmission electron microscopy (TEM) before it was fabricated into composites. The composites were prepared by melt blending with polypropylene (PP) at different fiber content of 2, 4, 6, 8, 10 and 12 wt. %. It showed that CNTs were successfully grown on carbon fibers at reaction temperature of 800oC and 900oC. Interfacial shear strength of CNT-coated fibers improved up to 499% compared to untreated fibers. Tensile properties increased with the increase of fiber loading from 2 wt. % - 10 wt. % and decreased at 12 wt. % fiber content. With addition of 10 wt. % of CNT-coated CFPP composites,the tensile strength and modulus increased up to 36% and 85%, respectively. CNTcoated CFPP composites were more resistant to deformation, but had lower strength when compared with commercial CFPP composites. The thermal stability of CNTcoated CFPP composites showed an increment compared to the untreated CFPP composite. As conclusion, CNT-coating treatment using parameters treated at reaction temperature of 800oC; 300 ml/min hydrogen flow rate and 1.0 g of ferrocene showed the most amounts of CNTs with fewer impurities which also exhibited the best performance in IFSS, tensile properties and highest onset degradation temperature, 325oC making it the best designation for this CNT-coating treatment using current thermal CVD set-up.